Protection of hepatocytes from cytotoxic T cell mediated killing by interferon-alpha. - Christian B Willberg; Scott M Ward; Reginald F Clayton; Nikolai V Naoumov; Christopher McCormick; Sandra Proto; Mark Harris; Arvind H Patel; Paul Klenerman (PLoS ONE)
Background Cellular immunity plays a key role in determining the outcome of hepatitis C virus (HCV) infection, although the majority of infections become persistent. The mechanisms behind persistence are still not clear; however, the primary site of infection, the liver, may be critical. We investigated the ability of CD8+ T-cells (CTL) to recognise and kill hepatocytes under cytokine stimulation. Methods/principle findings Resting hepatocytes cell lines expressed low levels of MHC Class I, but remained susceptible to CTL cytotoxicity. IFN-alpha treatment, in vitro, markedly increased hepatocyte MHC Class I expression, however, reduced sensitivity to CTL cytotoxicity. IFN-alpha stimulated hepatocyte lines were still able to present antigen and induce IFN-gamma expression in interacting CTL. Resistance to killing was not due to the inhibition of the FASL/FAS- pathway, as stimulated hepatocytes were still susceptible to FAS-mediated apoptosis. In vitro stimulation with IFN-alpha, or the introduction of a subgenomic HCV replicon into the HepG2 line, upregulated the expression of the granzyme-B inhibitor-proteinase inhibitor 9 (PI-9). PI-9 expression was also observed in liver tissue biopsies from patients with chronic HCV infection. Conclusion/significance IFN-alpha induces resistance in hepatocytes to perforin/granzyme mediate CTL killing pathways. One possible mechanism could be through the expression of the PI-9. Hindrance of CTL cytotoxicity could contribute to the chronicity of hepatic viral infections.